Fazlur Rahman dan Teori Double Movement: Definisi dan Aplikasi - Muhammad Umair; Hasani Ahmad Said (Jurnal test, 2023)
This paper discusses one of the Muslim intellectuals who played a major role in the development of the interpretation of the Koran, namely Fazlur Rahman. He is known for his theory of interpretation of the Koran which is called the double movement theory. This theory is interesting to discuss because it is a form of renewal of the methodology of interpreting the Koran in the modern era. So in this paper will be presented the definition of the theory and also how it is applied in life. Fazlur Rahman himself received religious education from an early age from his father and continued his studies to become a professor in the field of Islamic thought. This double movement theory has two movements, namely first by starting from looking at contemporary times towards the time when the Qur'an was revealed, then the second movement returns to the present. In general, this movement has a combination pattern of induction and deduction reasoning. This paper uses the method of analytical description of sources related to the research theme. So it can be concluded that the theory of the double movement is said to be relevant for use in the modern era where the meaning of the Koran becomes contextual and applicable. So that we are no longer trapped in the meaning of the Koran which is only textual. So it is hoped that in the future new contemporary interpretations of the Qur'an will emerge from this double movement theory.